IMPLEMENTASI PENDIDIKAN KARAKTER CERDAS FORMAT KLASIKAL (PKC-KA) DALAM LAYANAN INFORMASI - Ria Hayati (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2019)
Education is one of the basic assets of national development in Indonesia. National development starts from students as agents of change. Students have enormous tasks and responsibilities in society, so they must be smart in considering any issues that occur good or bad for their future. Smart krakter education is one of the new paradigms in learning that can build noble character in individuals to live a life in character and be smart in various fields and areas of life. The results of this study indicate: (1) Smart characters are specially made because having characters is not enough for students so intelligence is needed to complete them; (2) The intelligent character education model helps students be more active and; (3) Being able to actually relate various problems based on the topics discussed with character values arranged in a pocket book.Keywords: PKC-KA, Information Services